(untitled) (Journal of Environmental Bioremediation and Toxicology, 2022)
Acetamiprid is a kind of broad-spectrum systemic pesticide that works on the nicotinic acetylcholine receptor. This chemical disrupts the transmission of a signal and causes a buildup of neurotransmitters, which leads to pests being paralyzed and eventually dying as a result. The calibration curve for the detection of acetamiprid utilizing a gold nanoparticle-based visual aptasensor showed a sigmoidal shape profile; hence, the 5-PL or 4-PL model should be used to fit the data rather than a linear model. The result of the error function analysis shows that the simpler 4-PL model is more reliable having smaller AICc, R2 and adjR2, values whilst the other error functions such as RMSE, BIC and HQF, BF and AF values indicated that the 5-PL model shows that the 5-PL model was marginally superior to the 4-PL. As the 95% confidence interval overlap, the IC50 values were deemed not significantly different, and when this occur, based on Occam’s razor, the model having a lower number of parameters, which was 4-PL, should be chosen instead. The 4-PL equation produced a value for the LOD of 0.159 mM, and the confidence interval for 95 percent of the results ranged from 0.132 to 0.177. According to the first study, the LOD was 3.81 mM, and the calculated LOD using 4-PL model with pooled standard deviations was much more sensitive. This indicates that utilizing only the linear portion of a sigmoidal curve to report the LOD values gave a less sensitive value than it should be.